Revisiting the Classical German Idea of the University (on the Nationalization of a Modern Institution) - Kwiek, Marek (My University, 2008)
The aim of the paper is to provide a philosophical and historical background to current discussions about the changing relationships between the university and the state through revisiting the classical “Humboldtian” model of the university as discussed in classical German philosophy. This historical detour is intended to highlight the cultural rootedness of the modern idea of the university, and its close links to the idea of the modern national state. The paper discusses the idea of the university as it emerges from the philosophy of Wilhelm von Humbold, Johann Gottlieb Fichte and Friedrich Schleiermacher, as well as – in the 20th century – Karl Jaspers and Jürgen Habermas. More detailed questions discussed include the historical pact between the modern university and the modern nation-state, the main principles of the Humboldtian university, the process of the nationalization of European universities, the national aspect of the German idea of culture (Bildung), and the tension between the pursuit of truth and public responsibilities of the modern university. In discussing current and future missions and roles of the institution of the university today, it can be useful to revisit its foundational (modern) German idea. In thinking about its future, it can be constructive to reflect on the evident current tensions between traditional modern expectations of the university and the new expectations intensified by the emergence of knowledge-based societies and market-driven economies. From the perspective of the tensions between old and new tasks of the university, it is useful to look back at the turning point in its history.
Keywords: modern university; modern institution; Wilhelm von Humboldt; German idea of the university; Humboldtian university; classical idea of the university; German university model; Lehrfreiheit; Lernfreiheit; Gottlieb Fichte; German Idealists; Friedrich Schleiermacher; Karl Jaspers; Jurgen Habermas; the nation-state; national state; social pact; European universities; history of European universities; German philosophy